Growth of financing opportunities for small and medium-sized businesses in the digitalization of the economy context - N. I. Morozko; N. I. Morozko (Вестник университета)
The subject of the study is the methods of financing small and medium-sized businesses based on the use of investment platforms. The purpose of the article is to study the mechanisms for investing in small and medium-sized businesses in the digital economy based on a systematic approach. The article reveals the problems of lending to small and medium-sized businesses that hinder business development in modern conditions. Emphasis is placed on the mechanism of using investment platforms. The role of using crowdfunding technology is revealed. It is an affordable way to finance the activities of companies that do not have a credit history and collateral for obtaining a loan from banks. The stages of the investment process based on the use of the investment platform are outlined. The advantages and disadvantages of investment platforms for financing small and medium-sized businesses have been identified. A detailed analysis of the most common investment platforms in Russia has been carried out. It is emphasized that the study of positive and negative aspects in the system of crowdfunding relations should have a favorable impact on this direction of financing and provide investment platforms with a significant influx of investors.